2011
DOI: 10.1074/jbc.m111.253443
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNase L and RNA-dependent Protein Kinase (PKR) by Sunitinib Impairs Antiviral Innate Immunity

Abstract: RNase L and RNA-dependent protein kinase (PKR) are effectors of the interferon antiviral response that share homology in their pseudokinase and protein kinase domains, respectively. Sunitinib is an orally available, ATP-competitive inhibitor of VEGF and PDGF receptors used clinically to suppress angiogenesis and tumor growth. Sunitinib also impacts IRE1, an endoplasmic reticulum protein involved in the unfolded protein response that is closely related to RNase L. Here, we report that sunitinib is a potent inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 39 publications
(49 reference statements)
2
60
0
Order By: Relevance
“…PKR is therefore implicated in the integration and transmission of signals to the translational machinery as well as to factors such as STAT, IFN regulatory factor 1, p53, Jun Nterminal protein kinase (JNK), p38, ATF-3, and NF-B (48,121,125). PKR overexpression decreases-whereas its inhibition increases-the expression levels of several viruses (34,72,106,109,117). The cellular function of PKR on cell growth appears to be more complicated, because its upregulation or overexpression can inhibit the growth of some tumor cells, whereas an upregulation of PKR has been identified in some malignancies (13,104,141).…”
Section: Binding To Pkrmentioning
confidence: 99%
“…PKR is therefore implicated in the integration and transmission of signals to the translational machinery as well as to factors such as STAT, IFN regulatory factor 1, p53, Jun Nterminal protein kinase (JNK), p38, ATF-3, and NF-B (48,121,125). PKR overexpression decreases-whereas its inhibition increases-the expression levels of several viruses (34,72,106,109,117). The cellular function of PKR on cell growth appears to be more complicated, because its upregulation or overexpression can inhibit the growth of some tumor cells, whereas an upregulation of PKR has been identified in some malignancies (13,104,141).…”
Section: Binding To Pkrmentioning
confidence: 99%
“…Interestingly, the RNase L pseudokinase domain is critical for coordinating 2-5A binding (39,40) and homodimerization (33,34) that occur upon its activation. Furthermore, the ATP competitive kinase inhibitor sunitinib was recently shown to bind the ATP pocket within this domain and inhibit RNase L activation (93). Together, these studies establish a central role for the pseudokinase domain in RNase L activation and suggest that heterologous proteins that interact in this domain may positively or negatively impact RNase L activity as a novel mechanism to modulate its biologic functions.…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that inhibition of PKR represents an interesting strategy for neuroprotection, and preventing the cell death induced by ER stress in cultured human neuroblastoma cells (16,36,48,49,51,106,139). PKR was constitutively activated in FA-C cells, which contributed to the hypersensitivity of bone marrow progenitor cells to growth repression mediated by the inhibitory cytokines IFN-c and FIG.…”
Section: And Pangmentioning
confidence: 98%